DOP48 Key Anti-Inflammatory Faecalibacterium prausnitzii is Heterogeneous and Diverse in the East and West and in Health and Crohn's disease. The ENIGMA study. (30th January 2023) - Teh, J J; Kang, S; Leonard, A; Zhang, J; Hu, J; Hamilton, A L; Wilson-O'Brien, A; Trakman, G L; Lin, W; Ching, J; Sung, J J Y; Yu, J; et al.
Abstract: Background: There is insufficient knowledge about the key characteristics of the pathogenic and protective bacteria in inflammatory bowel disease. The ENIGMA study aimed to identify the phylogenetic and functional characteristics of Faecalibacterium prausnitzii, considered a protective "anti-inflammatory" bacterium, in both health and Crohn's disease in populations in the West (high Crohn's incidence) and Hong Kong (rapidly increasing Crohn's incidence). Methods: Total DNA was extracted from tissue (right colon and terminal ileum) and stool collected from case-control cohorts in Hong Kong (n=51; 30 Crohn's, 21 controls) and Australia (n=49; 29 Crohn's, 20 controls). In parallel, the colonic mucosa-associated microbiota (MAM) for each subject was cultured from anaerobically preserved tissue. Shotgun metagenomic sequencing was used to characterise the stool and colonic MAM, augmented with 16S rRNA gene profiling and F. prausnitzii qPCR. The HUMANn3 and/or QIIME2 packages were used for the taxonomic and/or functional characterisation of the datasets. Metagenome-assembled genomes (MAG) were also produced from colonic MAM datasets using the MetaWRAP pipeline, and taxonomy deduced using the Genome Taxonomy Database-Tool kit (GTDB-tk). Results: F. prausnitzii was detected in all case-control cohorts from Hong Kong and Australia. However, the prevalence was greater for the colonic MAM cultures of the Australian subjects, which provided 24/32 high-quality Faecalibacterium -affiliated MAG. No less than 6 different species-level lineages were predicted by GTDB-tk, and a similar phylogeny predicted using the gene encoding immunomodulatory peptides (mam). Functional features for the MAG from Crohn's disease and control subjects were compared, and genes involved with histidine, riboflavin, purine and pyrimidine metabolism, pentose phosphate pathway, and oxidoreductases were enriched in the control subject MAG. In contrast, MAG derived from Crohn's disease subjects possessed more functions putatively assigned to antibiotic resistance mechanisms and other protective functions. Differences were also observed in the carbohydrate-active enzyme profiles of the MAG recovered from Crohn's disease and control subjects. Conclusion: The populations of F. prausnitzii recovered from the colonic mucosa associated microbiota are both diverse and vary between Crohn's disease and control subjects in both countries. The differences include metabolic and physiological characteristics. Therapeutic modification of F. prausnitzii needs to consider phylogenetic and functional characteristics. The ENIGMA study is supported by a grant from the Leona M. and Harry B. Helmsley Charitable Trust